(untitled) (e-Proceedings of the Faculty of Agriculture International Conference, 2023)
Wood ash is one of the commonly available organic wastes in Nigeria because firewood is a common source of fuel for both rural and urban dwellers and can become an important alternative source of inorganic potassium especially for farmers in areas with acidic soils. Treatments consisted of the application of inorganic fertilizer sources (0 kg ha-1, 130.44 kg ha-1 urea and 300 kg ha-1 NPK 20:10:10) and wood ash (0 t ha-1, 5 t ha-1 ash and 10 t ha-1 ash) to garden egg seedlings in the field using 3 x 3 factorial experiment in randomized complete block design with three replications. Main effect of wood ash showed significant (p ≤ 0.05) fruit yield in this order: 10 t ha-1 of wood ash > control > 5 t ha-1 of wood ash. The main effect of inorganic fertilizer sources on fruit yield followed this sequence: 300 kg ha-1 NPK 20:10:10 > 130.44 kg ha-1 Urea > control. The interaction of 10 t ha-1 of wood ash and 300 kg ha-1 NPK 20:10:10 produced highest fruit yield (57 t ha-1) while 5 t ha-1 of wood ash produced lowest fruit yield (10.70 t ha-1). Therefore, the application of integrated 10 t ha-1 of wood ash and 300 kg ha-1 NPK 20:10:10 for improved growth and yield of garden egg is recommended to farmers in Awka.